2010
DOI: 10.1111/j.1365-2265.2009.03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of short‐term iodide supplementation to antithyroid drug treatment of thyrotoxicosis due to Graves’ disease

Abstract: Combined treatment with MMI and KI improved the short-term control of Graves' hyperthyroidism and was not associated with worsening hyperthyroidism or induction of thionamide resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In a previous study, the group treated with MMI and KI showed more significant improvement of thyroid function than the group with only MMI at 2 -4 weeks after the therapy. From 8 weeks downward, this significant improvement was not observed [10]. These results suggest that KI contributed to normalization of thyroid function at the early period of GD treatment.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…In a previous study, the group treated with MMI and KI showed more significant improvement of thyroid function than the group with only MMI at 2 -4 weeks after the therapy. From 8 weeks downward, this significant improvement was not observed [10]. These results suggest that KI contributed to normalization of thyroid function at the early period of GD treatment.…”
Section: Discussionmentioning
confidence: 56%
“…In other words, a role of KI for FT4 normalization is limited and relatively short. So, collecting together our finding and the previous finding [10], the cessation of KI or tapering of There is a report that excess iodine increased thyroid volume of GD patient [23]. Iodine, also known as an immune stimulant, may precipitate the onset of autoimmune thyroid disease and may be also directly toxic to the thyroid epithelial cell [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations